Atividades complementares para o desenvolvimento da escrita alfabética com alunos do 2º ano em estágio présilábico - Macêdo, Rosemary Gomes (2015)
The present dissertation has the objective of contributing to the learning improvement of children who are still undergoing their literacy studies. It is known that the early years of school life are the right time to prevent Functional Illiteracy. Children undergoing literacy studies do not learn to read and write by themselves, for they need a systematic and intense teaching-learning context along with the presence of a mediator who can provide them the necessary conditions to acquire such skills in the correct time; during their literacy studies. This dissertations proposes the execution of systematic activities aiming the development of the alphabetic writing in children of the 2nd year of elementary school who are still in the Pre-Syllabic level of writing. The activities performed were based in the studies of Lemle (1999) and Scliar-Cabral (2013), aiming the analysis of the improvement among the participating children by punctuating the improvements and difficulties along the process. To do so, writing tests were performed to analyze the improvement of the students, which could be divided into: (a) Initial Evaluation (Initial Diagnosis), to detect the subjects’ writing levels; (b) Execution of Practical Activities: initially aimed to literacy preparation, approaching the five problems described by Lemle (1999), followed by activities proposed by Scliar-Cabral (2013) and (c) a re-evaluation of the students’ writing levels (Final Diagnosis). The analysis of these activities application showed that they contributed to an improvement in the participants’ writing skills. Final Diagnosis pointed out that; out of 7 children who started in the Pre-Syllabic level, 2 advanced to the Alphabetic level, 2 to the Syllabic-Alphabetic level and 3 to the Syllabic level. These results show that when students are lead, through practical activities, to reflect over the Alphabetic Writing System, they improved their knowledge regarding this system e started to formulate hypothesis in the record of their writing. It is estimated that the objectives proposed for this research were achieved, for every participant presented some degree of improvement in their writing and started to create syllabic hypothesis over this system, the latter are responsible for the first tries of establishing relationships between the sonorous context and written language, period considered vital for the process of comprehension of the alphabetic writing.